Changes in arthroscopic training and education among German-speaking surgical residents: a prospective survey from 2020 and 2024 - Schmidt, Sebastian; Mengis, Natalie; Navas, Luis; Offerhaus, Christoph; Watrinet, Julius; Krahl, Daniel; Leutheuser, Sebastian (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
Arthroscopy has emerged as a crucial technique in modern orthopedic surgery, offering significant advantages over traditional open procedures. However, the steep learning curve and the need for advanced psychomotor skills presents challenges in training residents effectively. This study aimed to assess the development of arthroscopic skills, research involvement, and the impact of the COVID-19 pandemic arthroscopic training among residents in Germany. A prospective cross-sectional survey was conducted among members of the German-speaking Society for Arthroscopy and Joint Surgery (AGA) in two periods: March-April 2020 and March-April 2024. A total of 730 residents were invited to participate with response rates of 38.5% (n = 281) in 2020 and 30.5% (n = 223) in 2024. The survey included questions on demographic data, arthroscopic experience, research activities, participation in cadaver workshops and courses, and subjective perceptions of training. The study revealed significant arthroscopic experience variability (p< 0.001) with no significant differences in independently performed procedures between the 2020 and 2024 cohorts. However, there was a significant association between training year and the number of independently performed arthroscopies (p = 0.002). The COVID-19 pandemic led to a partial shift towards digital learning formats with a reduction in hands-on training opportunities. Despite these challenges, the volume of arthroscopies performed and the amount of research involvement remained stable. The data also indicated a trend towards outsourcing surgical training to external courses and organizations. Despite a subjective worsening of training conditions in the medium term, the volume of arthroscopies, course participation, and research activity of German-speaking residents in orthopedic and trauma surgery remains unchanged, although there is still a substantial variability in arthroscopy case volume. To compensate for this, training is increasingly being outsourced and improved in-house training concepts should be established.